Anthelmintic Effect of Aniseed (Pimpinella anisum L.) Ethanolic Extract on Ascaris suum Goeze In Vitro - Safitri, Okky Dhevi; Dirgahayu, Paramasari; Haryati, Sri (Nexus Kedokteran Translasional, 2016)
Introduction: Aniseed (Pimpinella anisum L.) contain trans-anethole and estragole that have anthelmintic effect. This study aimed to determine the anthelmintic effect of aniseed (Pimpinella anisum L.) ethanolic extract on Ascaris suum Goeze in vitro. Methods: The study was a laboratory experimental research using the posttest only controlled group design. Subjects were adult Ascaris suum Goeze. The sampling technique used was purposive sampling. Subjects were divided into 7 groups: NaCl 0,9% (negative control), pyrantel pamoate 5 mg/ml (positive control), aniseed ethanolic extract 200, 225, 250, 275 and 300 mg/ml. Each group consisted of 5 worms, replication performed 5 times. Worms immersed in the solution at 100 ml and incubated at 37Â°C. Observations of individual worms were made up until all worms in treated group dies. Mean death time of each worms were analyzed by SPSS program version 20 using One Sample Kolmogorov-Smirnov normality test, test of homogeneity of variances (Levene test), One Way ANOVA parametric test and LSD Post Hoc test. Results: Mean death time of each worms Ascaris suum Goeze on aniseed ethanolic extract group concentration 200, 225, 250, 275 and 300 mg/ml were 1.22 Â±0.14 hours, 1.01Â±0.16 hours, 0.80Â±0,22 hours, 0.64Â±0.21 hours, and 0.61Â±0.19 hours, the positive control group was 0.90Â±0.22 hours, and negative control group did not show wormâs death. Normality and homogeneity test showed normal distribution and homogeneity of the data. One Way ANOVA test showed the difference of mean death time were all significant on all group, LSD Post Hoc test showed the significant mean death time were found on group concentration â¤ 250 mg/ml. Conclusion: Aniseed (Pimpinella anisum L.) ethanolic extract has anthelmintic effect on Ascaris suum Goeze in vitro. Anthelmintic effect on concentration â¤ 225 mg/ml was lower than that on pyrantel pamoate concentration 5 mg/ml, and on concentration â¥ 250 mg/ml was higher than that on pyrantel pamoate concentration 5 mg/ml. Keywords: Aniseed (Pimpinella anisum L.) ethanolic extract, Ascaris suum Goeze, Anthelmintic.